A Study of Corporate Governance Practices In India: Examining the implications of corporate governance practices in the Indian context (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Corporate governance (CG) has emerged as a very importantideal. The reason is, today companies are substantially contributing to theoverall growth and development, particularly in emerging economies such asIndia and a healthy investment environment is vital. To overcome thelimitations of the partnership form of business, mainly on account of thelimited availability of capital, the corporate form of business has gainedwidespread acceptability, succeeded gradually and expanded worldwide. However,not all companies are managed successfully. There has been a spree of corporatefrauds worldwide, e.g., Enron in the United States (US) and more recently inIndia, Satyam Computers. The latter had accounting and auditing flaws apartfrom lack of accountability and oversight by Independent Directors at Boardmeetings. There was no whistle-blowing in case of Satyam Computers unlikeEnron. The Satyam Computers revelation was an outcome of a takeover attempt. Iteroded the wealth of shareholders. From this fraud it is evident that we need to review theenforcement of CG practices. The role of the Ministry of Corporate Affairs(MCA) as one of the stakeholders in case of Satyam Computers has beencommendable especially in appointing reputed members on the Board immediatelyafter the fraud, in order to restore confidence among investors, customers,employees and to revive the company. This initiative by the government alsoencouraged the stock markets to some extent.